Participant Experiences of Transcranial Direct Current Stimulation (tDCS) as a Treatment for Antipsychotic Medication Induced Weight Gain - Grycuk, Luiza; Moruzzi, Francesca; Bardjesteh, Elena; Gaughran, Fiona; Campbell, Iain C.; Schmidt, Ulrike (Frontiers in Psychology, 2021)
Background: Despite the growing number of studies on the use of non-invasive brain stimulation in people with schizophrenia, there is limited research on participant views of such treatment methods. Aim: Explore participant experiences and perceptions of transcranial direct current stimulation (tDCS). Methods: Twelve people with schizophrenia took part in semi-structured interviews after having completed 5 sessions of tDCS. Thematic analysis was used to identify codes and themes. Results: Five themes were identified: (1) motivation for study enrolment; (2) concerns about tDCS; (3) factors reducing the fear of tDCS; (4) experience of tDCS; (5) perceived effects of tDCS. Conclusions: The study provides insight into the perceptions and experiences of each individual. Participants were concerned about the safety of tDCS and associated it with invasive procedures such as electroconvulsive therapy and lobotomy. Educational materials and a good relationship with the researcher played an important role in reducing the fear of brain stimulation. All participants described tDCS as uncomfortable, however, agreed that unpleasant sensations only lasted for a short while (20 second to 5 minutes). After the first session, participants no longer felt anxious about the remaining ones. Strategies to improve treatment experience and study recruitment have been identified.